THE MEDIATING ROLE OF ORGANIZATIONAL AGILITY IN THE RELATIONSHIP BETWEEN DIGITAL TRANSFORMATION AND FIRM PERFORMANCE - Syarkani, Yofy (Journal of Social and Economics Research, 2025)
This study investigates the mediating role of organizational agility in the relationship between digital transformation and firm performance through a comprehensive literature review. As digital technologies increasingly reshape competitive dynamics, organizations are compelled to adapt rapidly to sustain operational efficiency and strategic relevance. While existing literature has widely acknowledged the positive impact of digital transformation on performance, the mechanisms through which this transformation translates into measurable outcomes remain underexplored. Organizational agility has emerged as a critical capability that enables firms to navigate uncertainty and capitalize on digital investments. This article synthesizes findings from peer-reviewed sources published between 2015 and 2024, accessed through Scopus, Web of Science, and Google Scholar. The review reveals that agility enhances the responsiveness, adaptability, and innovation potential of firms undergoing digital transformation. It further identifies agility as a strategic mediator that bridges digital initiatives with superior performance metrics such as profitability, market share, and customer satisfaction. The findings contribute to a deeper understanding of the dynamic capabilities perspective in digital contexts. This study also highlights conceptual gaps and calls for empirical research to validate the mediating effect of agility across industries and firm sizes. The article offers theoretical insights and practical guidance for managers seeking to align digital strategies with organizational capabilities to drive sustainable performance.